„Quicquid in Euripide, tragicorum principe, memorabile est” – forma gnomiczna Eurypidesa oraz jej recepcja w XVI wieku - Czerwińska, Jadwiga; Koźluk, Magdalena (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza, 2008)
The works of Euripides contain a rich and great variety of gnomic phrases. These provide the opportunity for an examination of the differences and the functions of gnomes, their kinds and themes. The evidence for the reception of gnomic forms are the editiones principes of Euripidean tragedies that appeared in 16th century literature and the publication of collections of maxims during the period.

Due to their formal and thematic value, ancient sententiae were very popular in Greek literature. They were frequently used by different authors who were aware of their great esthetic, rhetoric and didactic potential. This feature distinguishes the works of the last of the three great tragedians – Euripides. His plays which contain a great variety of gnomic phrases, provide an opportunity of an examination of the differentiation and the function of gnomes in literature, especially in his dramas, and of the kinds of maxims that were used by the tragedian. Treated as an exemplum, they can be considered under three aspects: 1. the conciseness of gnomes; 2. their ethical character; 3. the reception of gnomes from the point of view of their form and content (morality). When they occur in later literature, gnomes of ancient authors, including Euripides, retain their moral capacity and freshness. They are present during the medieval period, but they fourish and reach their prime during the Renaissance. In the second part of our analysis, we examine the role played by gnomes in Renaissance texts: We consider the main sources of sentences from which the humanists drew ancient maxims (forilegia, fores, margueritae, ars dictaminis, collections of loci communes, collections of emblems. We pay particular attention to the major part played in the translatio studii of sentences derived from Euripidean tragedies by 1. the relatively rapid appearing of editiones principes of all the tragedies, 2. the publication of Erasmus of Rotterdam’s monumental work, the Adagia, and also 3. The publication of the Aristologia Euripidea (Basel, Johannes Oporinus, 1559). Finally, we consider the issue of the borrowing of sentences in relation to literary ethics.
„Quicquid in Euripide, tragicorum principe, memorabile est” – The Gnomic Form in Euripides and its Reception in the 16th Century
Keywords: Euripides; Sententia; Translatio studii; Literary ethics; Imitation; Renaissance